Sărăcia energetică: impactul social al reformei preţurilor energiei asupra standardului de viaţă - Zamfir, Cătălin; Dumitru, Mihai; Mihăilescu, Adina; Stanciu, Mariana; Zamfir, Elena; Bădescu, Ilie; Glodeanu, Ion; Şerban, Adela (Calitatea Vieții, 2015)
This study deals with the social impact, vulnerabilities, and social problems brought about by the reform of the energy system and the creation of the national energy market. The findings point to the critical, structural problems of household energy consumption: the poverty shock that will include about 50% of the Romanian population, the issue of housing as a source of energy inefficiency, the crisis of the public winter heating Utilities, shortcomings in consumer protection, the dijficult energy situation in rural areas, the number of vulnerable consumers, corruption in the energy industry etc. The high increase of energy prices and the rise in energy poverty and the number of vulnerable consumers compel to a criticai evaluation and redesign of the social protection system. The analysis uses naţional and internaţional statistical data regarding energy consumption, poverty and material deprivation collected by Romanian and European public institutions. In addition, we use survey data of the Research Institute for Quality of Life regarding the standard of living, poverty or the living wage. In the following 2–3 years, electricity and gas prices are expected to double, which will have deep consequences no only on the social situation of vulnerable consumers, but also on public policies, especially for energy regulation institutions. For this reason, the study features a set of policy recommendations.